Epilepsy Course and Developmental Trajectories in STXBP1-DEE. (31st May 2022) - Balagura, Ganna; Xian, Julie; Riva, Antonella; Marchese, Francesca; Ben Zeev, Bruria; Rios, Loreto; Sirsi, Deepa; Accorsi, Patrizia; Amadori, Elisabetta; Astrea, Guja; Baldassari, Simona; Beccaria, Francesca; et al.
Abstract : Background and Objectives: Clinical manifestations in STXBP1 developmental and epileptic encephalopathy (DEE) vary in severity and outcome, and the genotypic spectrum is diverse. We aim to trace the neurodevelopmental trajectories in individuals with STXBP1 -DEE and dissect the relationship between neurodevelopment and epilepsy. Methods: Retrospective standardized clinical data were collected through international collaboration. A composite neurodevelopmental score system compared the developmental trajectories in STXBP1 -DEE. Results: Forty-eight patients with de novo STXBP1 variants and a history of epilepsy were included (age range at the time of the study: 10 months to 35 years, mean 8.5 years). At the time of inclusion, 65% of individuals (31/48) had active epilepsy, whereas 35% (17/48) were seizure free, and 76% of those (13/17) achieved remission within the first year of life. Twenty-two individuals (46%) showed signs of developmental impairment and/or neurologic abnormalities before epilepsy onset. Age at seizure onset correlated with severity of developmental outcome and the developmental milestones achieved, with a later seizure onset associated with better developmental outcome. In contrast, age at seizure remission and epilepsy duration did not affect neurodevelopmental outcomes. Overall, we did not observe a clear genotype-phenotype correlation, but monozygotic twins with de novo STXBP1 variant showed similar phenotype and parallel disease course. Discussion: The disease course in STXBP1 -DEE presents with 2 main trajectories, with either early seizure remission or drug-resistant epilepsy, and a range of neurodevelopmental outcomes from mild to profound intellectual disability. Age at seizure onset is the only epilepsy-related feature associated with neurodevelopment outcome. These findings can inform future dedicated natural history studies and trial design.